FACTORS THAT INFLUENCE THE INTEREST IN THE UTILIZATION OF SHARIA FINANCIAL TECHNOLOGY ON MILLENNIALS AND GENERATION Z - Amir Hamzah; Nurfania Sukma (IAIN Manado, 2021)
The purpose of this research is to analyze the effect of perceived ease of use, perceived benefits, perceived risk, trust, and religiosity on behavioral intentions of Islamic financial technology in the millennial generation and Generation Z in Kuningan Regency. The type of research used is quantitative research, with descriptive and verification research methods. The primary data in this study were obtained by using a questionnaire distributed through Google Form. The population in this study is the millennial generation and Generation Z in Kuningan Regency with a research sample of 125 respondents. The sampling method used in this research is non-probability sampling with a purposive sampling technique. The data analysis technique used is Structural Equation SEM-PLS. Results of this study indicate that the variables of perceived ease of use, perceived benefits, perceived risk, trust, and religiosity have a significant positive effect on behavioral intentions of Islamic financial technology in the millennial generation and generations in Kuningan Regency.